PENGARUH BIOCHAR SERBUK KAYU DURIAN TERHADAP KARAKTERISTIK TANAH SULFAT MASAM DALAM MENGURANGI EMISI GAS METANA - Evy Setiawati; Sugeng Prijono; Diah Mardiana; S Soemarno (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
Organic matter in the soil can provide nutrients to plants. The objectives of this study were to analyze soil characteristics after incubation using biochar at various doses, and to calculate the reduction of methane gas emissions from incubated soils. The treatments were (1) soil control (T0); (2) 4 t ha-1 biochar + soil (T1); (3) 8 t ha-1 biochar + soil (T2); (4) 12 t ha-1 biochar + soil (T3); (5) 16 t ha-1 biochar + soil (T4); (6) 20 t ha-1 biochar + soil (T5). The soil of each treatment was incubated for 30, 60, and 90 days. Observations were made on pH, exchangeable cations (Ca, Mg, K, Na) and cation exchange capacity (CEC). Methane gas emissions were measured at 30, 60, and 90 days after planting. The percentage increase in incubation soil pH for 30 days was 3.13-48.71%, 60 days was 3.06-21.26%, and 90 days was 0.41-28.26%. CEC also increased from 28.83 to 37.46 me 100 g-1 (29.95%) at 30 days, 27.63-36.16 me 100 g-1 (30.86%) at 60 days, and 26.07-35.01 me 100 g-1 (34.28%) at 90 days. Exchangeable Ca, and Mg was not significantly different for all biochar doses and incubation times. The reduction in methane gas emissions ranged from 9.57-18.08% (30 days); 33.13-35.23% (60 days); and 46.08-73.25% (90 days).